(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the linguistic phenomenon of substantivization of adjectives, a process by which adjectives transform into nouns to represent abstract concepts, groups, or qualities. The article first defines substantivization and explains how it allows adjectives to function as nouns through the use of definite articles, plural markers, or suffixes. It then examines how different languages, including English, German, French, and Spanish, apply substantivization, highlighting examples like "the rich" or "les jeunes." In addition, the article discusses the importance of substantivization in enhancing language efficiency, flexibility, and expressiveness. It enables speakers to encapsulate complex ideas concisely, contributing to clearer and more nuanced communication. The article concludes by noting that substantivization enriches language’s poetic and figurative capabilities, making it an invaluable tool across diverse linguistic contexts.